A novel dispersion monitoring technique in W-band radio-over-fiber signals using clustering on asynchronous histograms (2014)
ABSTRACT: Radio over Fiber (RoF) systems have been proposed as a promising solution for transmitting radiofrequency signals at high data rates over long distances. To reach data rates in the Gbps range, studies indicate using the W-Band (75 -110 GHz). However, in this frequency band, chromatic dispersion becomes an issue that increases the bit-error-rate. This paper presents a novel digital dispersion monitoring technique for RoF systems based on asynchronous histogram analysis. This method quantifies the intensity level of the distortion of a radiofrequency demodulated signal by a dispersion factor. This dispersion factor is calculated using an enhanced clustering approach, which carries out a Gaussian fitting technique through the expectation-maximization algorithm. Dispersion monitoring was performed on radiofrequency transmission simulations using non-return-to-zero and binary phase-shift keying modulated signals over 80 km of optical fiber at 60, 75 and 100 GHz. The bit error rate is estimated and compared to the dispersion factor, showing that the behavior of the dispersion effects are not proportional to the increase of carrier frequency, bit rate and distances. This novel monitoring method can be used to estimate the feasibility of RoF systems for future hybrid networks under specific transmission parameters such as fiber length, modulation format, and carrier frequency.